2023
DOI: 10.1002/14651858.cd013472.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Musical and vocal interventions to improve neurodevelopmental outcomes for preterm infants

Friederike B Haslbeck,
Katharina Mueller,
Tanja Karen
et al.

Abstract: Musical and vocal interventions to improve neurodevelopmental outcomes for preterm infants (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 170 publications
0
4
0
Order By: Relevance
“…Our results further validated this result, as music can increase the blood oxygen saturation of neonates during and after painful procedures. According to a recent systematic review, music/vocal interventions could reduce the heart rate in preterm infants during procedures, and the effect was greater after the procedures ( 36 ). Nevertheless, music did not have an obvious advantage in decreasing the peak heart rate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further validated this result, as music can increase the blood oxygen saturation of neonates during and after painful procedures. According to a recent systematic review, music/vocal interventions could reduce the heart rate in preterm infants during procedures, and the effect was greater after the procedures ( 36 ). Nevertheless, music did not have an obvious advantage in decreasing the peak heart rate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results presented in this meta-analysis, Cochrane developed a systematic review involving 25 RCTs, 1532 neonates, and 691 parents, to evaluate the effectiveness of using music or vocal interventions on the neurodevelopment of premature babies and their physiological parameters [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, music is capable of reducing the HR of premature babies, especially after the intervention, but it does not increase oxygen saturation, nor does it reduce the RR of babies or the intensity of the parents' anxiety. It is noteworthy that no negative effects were found associated with the musical intervention [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, research has also indicated a gap between potential benefits and actual outcomes. This discrepancy, highlighted in studies such as that by Haslbeck et al, 2 suggests that the practical application of music in this context may not fully meet expectations.…”
mentioning
confidence: 96%